Counterfactual Reasoning and Conceptual Blending in Political Discourse - Babić-Antić, Jelena B.; Spasić, Dragana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Conceptual integration and blending are deeply embedded within the human cognition. They are a part of everyday life common for infants and adults alike. Without these fundamental cognitive operations there would be no advancement in any of the aspects of human progress. One small part, a product of these mental operations is “counterfactual reasoning”. This ability of human beings to “undo” reality is remarkable and pervasive in every aspect of life. The ability to operate with the unreal by producing counterfactuals has been a subject of many research projects. Our goal in this paper is to examine the frequency of their appearance in the political discourse, as well as to establish what exactly their purpose is, once they are present in the political discourse.
Keywords: political discourse; counterfactual reasoning; blending; conceptual integration